The results of Holter monitorization in patients receiving labetalol or lidocaine prior to intubation - Erhan, O.L.; Arslan, N.; Oysul, B.; Isik, A. (My University, 1990)
[Abstract Not Available]
Keywords: labetalol; lidocaine; adult; aged; article; blood pressure; clinical article; electrocardiography; endotracheal intubation; female; hemodynamic monitoring; holter monitoring; human; intravenous drug administration; laryngoscopy; male